(3TQM YbjOI GdEeGe ESeGYjd GdRjOis - (3CMeO GdbGTj GdeOjfjs ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfYe YdjfG hgOGfG ddESdGe CeG HYO ` abO hUdJ EdjfG hQbI YbH GdML ef SfI SJ hSJjf hGda ai EMOi UMajJgG YbjOI jRYe UGMHgG CfgG YbjOI GdaQb GdfGLjI s
(3BNQgG (B:s
(3Gddge CQfG GdMb MbkG hGQRbfG EJHGYg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B50s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI MQjVI ecJHI YeQ Hf CMeO GdYehOi GdYGeI s
Keywords: (3abg GdePGgH GdCNQis